2015
DOI: 10.1097/naq.0000000000000082
|View full text |Cite
|
Sign up to set email alerts
|

Bridge to Shared Governance

Abstract: Transforming health care systems to improve quality is the responsibility of nurse executives and frontline nurses alike, yet frontline nurses are often ill-prepared to share leadership and accountability needed for transformation. The aim of this qualitative study was to describe the process used to build leadership capacity of frontline nurses engaged in resolving operational failures interrupting nursing care. The leadership development process served to bridge staff transition to shared governance. This in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Three components structured methods used in top-down initiatives. There was a learning-based component (n = 10), which integrated an ‘innovating while learning’ element in the EDI process (eg, 77 , 66 , 94 ). All methods, except the competition-based method included a learning component.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three components structured methods used in top-down initiatives. There was a learning-based component (n = 10), which integrated an ‘innovating while learning’ element in the EDI process (eg, 77 , 66 , 94 ). All methods, except the competition-based method included a learning component.…”
Section: Resultsmentioning
confidence: 99%
“…While many methods (eg, participatory approach, design tools) naturally involved forming groups, these studies reported deliberate establishment of a group dedicated to innovation efforts. For example, a “frontline innovation group” 66 which “provided a forum to enhance empowerment … while seeking solutions to operational failures” (p. 75). Finally, a digital component was mentioned (n = 6) to promote the collection, brainstorming and visibility of employees’ ideas (eg, 51 , 75 ).…”
Section: Resultsmentioning
confidence: 99%
“…Resulting articles were eliminated if the objective was anything other than improving shared professional governance, if the objective was related only to spreading council structure to a new unit or shift (ie, night shift), or if no educational intervention was identified. Five articles remained, 2,10-13 one of which 2 used a validated tool (the IPNG) to measure the effectiveness of the educational intervention to improve RNs' perception of shared professional governance.…”
mentioning
confidence: 99%